An Axiomatization of the Banzhaf Index to Measure Influence in Qualitative Comparative Analysis - Haake, Claus-Jochen; Schneider, Martin (International Journal of Game Theory)
The Banzhaf power index can be used to quantify the explanatory power of single conditions in a configurational analysis that aims at identifying whether combinations of conditions are sufficient for an outcome. The latter method is an integral part of the Qualitative Comparative Analysis (QCA) approach. It is widely used in the literature, e.g., in the field of International Management. Haake and Schneider (2023) give a rigorous description of the connection between the empirical and game theoretic modeling. To justify that the Banzhaf index is an appropriate tool to measure the influence of a condition, this paper discusses a novel axiomatization of the Banzhaf index that uses axioms that are directly linked to the QCA methodology. As a side result, we demonstrate that in our model the Banzhaf index can be reinterpreted as an average of Shapley-Shubik indices.
Keywords: Banzhaf index; axiomatization; QCA; explanatory power

Modelling Hierarchical Configurations in Innovation Research With Two‐Step QCA: Methodological Recommendations and an Application to Workarounds - Sandfort, Luc; Hellweg, Talea Davina; Radermacher, Katharina; Schneider, Martin (Creativity and Innovation Management)
ABSTRACT Creativity and innovation are often understood as the result of a complex interplay of hierarchical factors, such as national, regional and firm characteristics, or between organisational and individual factors. While recent applications of qualitative comparative analysis (QCA) have begun to model such configurational links, their hierarchical nature has received little empirical attention. As this paper demonstrates, theories that posit hierarchical configurations can and should be explored using the two‐step variant of QCA. The paper outlines the potential of the method for the field of creativity and innovation and helps to navigate key modelling decisions. An illustrative study explores the occurrence of informal employee innovation behaviour—workarounds—based on the Ability‐Motivation‐Opportunity (AMO) framework. The results of the two‐step QCA are superior in terms of reduced limited diversity and complexity to those of the conventional one‐step QCA. Overall, the method has considerable potential for empirically capturing the complex, hierarchical interactions inherent in many innovation processes.

Verstecktes Innovationspotenzial: Entstehungsfaktoren von Workarounds. - Hellweg, Talea Davina; Radermacher, Katharina; Schneider, Martin; Sandfort, Luc Dana (PersonalQuarterly 2026(01))

Who are the Actively Participating Crowdworkers? A Qualitative Comparative Analysis of a German Text Creation PlatformSocio-Economic Studies, - Schneider, Martin; Hemsen, Paul; Kundisch, Dennis (management revue - Socio-Economic Studies, Special Issue “Digital Transformation of Work”.)

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

Digitales und prädiktives Kompetenzmanagement

HR-Praktiken als Ressourcenmanager: Wie die Schwächen flexibler und unflexibler Arbeitsmodelle kompensiert werden können. Studie Industrieverband Büro und Arbeitswelt e.V.. - Radermacher, Katharina; Schneider, Martin

Which Types of Workers Are Adversely Affected by Digital Transformation? Insights from the Task-Based Approach - Hellweg, Talea; Schneider, Martin (The Digital Twin of Humans. An Interdisciplinary Concept of Digital Working Environments in Industry 4.0)

Digital Twins in Flexible Online Work: Crowdworkers on German-Language Platforms - Hemsen, Paul; Reimann, Mareike; Schneider, Martin (The Digital Twin of Humans. An Interdisciplinary Concept of Digital Working Environments in Industry 4.0)

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Pilz, Sarah; Hellweg, Talea; Harteis, Christian; Rückert, Ulrich; Schneider, Martin (The Digital Twin of Humans. An Interdisciplinary Concept of Digital Working Environments in Industry 4.0)

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Die Politische Meinung)

Role (in-)congruity and the Catch 22 for female executives: how stereotyping contributes to the gender pay gap at top executive level - Diederich, Sarah; Iseke, Anja; Pull, Kerstin; Schneider, Martin (The International Journal of Human Resource Management)
Keywords: Management of Technology and Innovation; Organizational Behavior and Human Resource Management; Strategy and Management; Business and International Management; Industrial relations

Who Will Own Our Global Digital Twin: The Power of Genetic and Biographic Information to Shape Our Lives - Hellweg, Talea Davina; Schneider, Martin; Rückert, Ulrich; Harteis, Christian; Pilz, Sarah (The Digital Twin of Human)
Today, it is possible to collect and connect large amounts of digital data from various sources and life domains. This chapter examines the potential and the risks of this development from an interdisciplinary perspective. It defines the ‘global digital twin’ of a human being as the sum of all digitally stored information and predictive knowledge about a person. It points out that, compared to the digital twin of a machine, the human global digital twin is far more complex because it comprises the genetic code and the biographic code of a person. The genetic code contains not only a simple ‘construction plan’ but also hereditary information, in a form that is difficult to read. The biographic code contains all other information that can be assembled about a person, which is obtained via data from cameras, microphones, or other sensors, as well as general personal information. When the growing wealth of information concerning the genetic code and the biographical code is properly utilised, insights from biology and the behavioural sciences may be used to predict personal events such as health problems, job resignations, or even crimes. Because our own interests and those of private firms are partly in conflict over the use of this powerful knowledge, it is still unclear whether the global digital twins of humans will become a liberating or disciplining force for citizens. On the one hand, human beings are not machines: They are aware of their digital twin and therefore are able to influence it throughout their lives. Because of their free will, human beings are in general difficult to predict. Dystopias of full control over individual behaviour are therefore unlikely to materialise. On the other hand, private firms are beginning to take advantage of the available digital twins of humans by monopolising data access and by commercialising predictive knowledge. This is problematic because, unlike machines, human beings cannot only benefit from but also suffer due to their digital twins as they attempt to shape their own lives. We illustrate these issues with some examples and arrive at two conclusions: It is in the public interest for people to be granted more property rights over their personal global digital twins, and publicly funded research needs to become more interdisciplinary, much like private firms that have already begun to perform interdisciplinary research.

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Radermacher, Katharina; Schneider, Martin (Die Politische Meinung)

The DaimlerChrysler takeover failure revisited from a varieties-of-capitalism perspective - Riach, John Rankin Wood; Schneider, Martin (Cross Cultural and Strategic Management)
Purpose The purpose of this paper is to revisit the disastrous DaimlerChrysler AG takeover episode from 1998 to 2007 in order to arrive at a more comprehensive explanation of this and other merger and takeover failures based on institutional theory. Design/methodology/approach The case study is based on various secondary sources of information and on the insights that one of the authors gained from working for 14 years in various positions for Daimler-Benz and DaimlerChrysler. Findings DaimlerChrysler failed because top management made mistakes in trying to globalize the company. They were unable to realize possible synergies between the two companies, which brought complementary resources into the merger. Furthermore, they did not account for the institutional embeddedness of strategies when they adopted lean production globally, diffused the production system developed in Germany to other parts of the world and tried to implement a global stock enlisted in New York and Frankfurt. The underlying theoretical framework is relevant for other merger and acquisition cases. It features institutional embeddedness, path dependency and institutional arbitrage. Originality/value The paper develops an institutional perspective on DaimlerChrysler and on cross-border merger and acquisition failure more generally. The perspective is organized around the varieties-of-capitalism approach. This contribution is important because there is increasing dissatisfaction with the dominant explanation of cross-border merger and acquisition failure, which is based on the allegedly failed management of culture “clashes.”
Keywords: Organizational Behavior and Human Resource Management; Strategy and Management; Sociology and Political Science; Cultural Studies; Business and International Management

Identification of Human and Organizational Key Design Factors for Digital Maturity – A Fuzzy-Set Qualitative Comparative Analysis - Schneider, Martin; Hellweg, Talea Davina; Menzefricke, J. S. (Proceedings of the Design Society)
Abstract This paper examines how human and organizational factors need to be designed to achieve strong technological maturity of either the products or the production process. In a fuzzy-set qualitative comparative analysis (fs/QCA), a combination of intensive training and strong worker participation is found to be associated with strong technological maturity in the two organizational contexts: firms with a strong entrepreneurial culture and in large firms oriented towards customer-oriented innovation. Overall, the paper uncovers designs or causal recipes for a successful digital transformation.

Gier und andere Tugenden: Widersprüchliche Bewertungen der Marktwirtschaft in Oliver Stones Wall Street - Schneider, Martin (Erzähltes Geld Finanzmärkte und Krisen in Literatur, Film und Medien)

Urbane Arbeitsparadiese gestern und heute - Schneider, Martin (Urbane Kulturen und Räume Intermedial)

Personalökonomie und Personalpolitik: Grundlagen einer evidenzbasierten Praxis - Schneider, Martin; Sadowski, Dieter; Frick, Bernd; Warning, Susanne

Gier und andere Tugenden: Widersprüchliche Bewertungen der Marktwirtschaft ain Oliver Stones "Wall Street" - Schneider, Martin (Erzähltes Geld: Finanzmärkte und Krisen in Literatur, Film und Medien)